Fast one-pot laser-based fabrication of ZnO/TiO2-reduced graphene oxide nanocomposite for photocatalytic applications. (May 2023) - Manda, Abdullah A.; Haladu, Shamsuddeen A.; Elsayed, Khaled A.; Ibrahim Gaya, Umar; Alheshibri, Muidh; Al Baroot, Abbad; Çevik, Emre; Ercan, İsmail and Ercan, Filiz and Kayed, T.S. and Musa Magami, Saminu and Altamimi, Nafala A.
Highlights: ZnO-TiO2 -rGO nanocomposite was fabricated by laser ablation in liquid. The synthesis was accomplished in 30 min. Various characterization techniques confirm the formation of the nanocomposites. The nanocatalysts demonstrate excellent photodegradation of methylene blue. Abstract: Laser synthesis is rapidly emerging to be an efficient and unique method for the synthesis of a wide spectrum of nanomaterials owing to its ease of setup, simplicity, and generation of high-purity nanomaterials. This study explores a pulse laser ablation protocol in the synthesis of ZnO-TiO2 (ZT) and ZnO-TiO2 -reduced graphene oxide (ZT-rGO) nanocomposites. The effect of rGO loading (5 %, 10 %, and 20 %) was investigated on the nature of the crystalline nanostructures formed, the increased thermal stability achieved, and the effective removal of methylene blue dye. Following fabrication, the nanocatalyst materials were characterized by TEM, PXRD, SEM/EDX, AFM, UV–Vis, TGA, and FTIR. Using UV illumination, the as-synthesized photocatalysts were evaluated in the photodegradation of methylene blue (MB) as a model dye pollutant. Among the nanocomposites, the ZT-rGO 5 % shows the best photocatalytic activity by having a preferential rate constant of 0.149 min −1 . The nanocomposites were prepared in 30 min, providing 98.5 % MB removal within just 30 min, using 10 mg/L of MB and 20 mg/L of the catalyst. During the photodegradation process, the rGO component serves as an electron trap, thus enhancing the formation of holes which are the mainstay of any photocatalytic process. As demonstrated by the work reported, the laser ablation technique shows great promise in the fabrication of ZT-rGO nanocomposites and similar analogs relevant to the efficient decolorization of wastewater.